Methodology for estimating offshore wind turbine fatigue life under combined loads of wind, waves and ice at sub-zero temperatures - Milaković, Aleksandar-Saša (author); Braun, Moritz (author); Willems, Tom (author); Hendrikse, H. (author); Fischer, Claas (author); Ehlers, Sören (author) (2019)
Due to increasing trend of building offshore wind turbines (OWTs) in seas at high latitudes where seasonal sea ice occurs, novel methods for design of such structures are needed. Specifically, the effect of ice-induced vibrations (IIVs) on fatigue life of the structures is currently poorly understood. Therefore, the goal of this paper is to analyze the current state-of-the-art approach for estimating the ice loads contribution to the fatigue life of OWTs and identify the current knowledge gaps. Moreover, the paper proposes a methodology for developing a combined load spectrum of wind, waves and ice using numerical simulations, with an ultimate goal to develop applicable Gaßner curves characterizing the variable-amplitude nature of the loading pattern. Finally, the use of small-scale fatigue tests under sub-zero temperatures in order to develop the appropriate S-N and Gaßner curves is discussed. Green Open Access added to TU Delft Institutional Repository ‘You share, we take care!’ – Taverne project https://www.openaccess.nl/en/you-share-we-take-care Otherwise as indicated in the copyright section: the publisher is the copyright holder of this work and the author uses the Dutch legislation to make this work public. Offshore Engineering